If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2y + -3 + -9x = 0 Reorder the terms: -3 + 5x + -9x + 2y = 0 Combine like terms: 5x + -9x = -4x -3 + -4x + 2y = 0 Solving -3 + -4x + 2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + -4x + 3 + 2y = 0 + 3 Reorder the terms: -3 + 3 + -4x + 2y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -4x + 2y = 0 + 3 -4x + 2y = 0 + 3 Combine like terms: 0 + 3 = 3 -4x + 2y = 3 Add '-2y' to each side of the equation. -4x + 2y + -2y = 3 + -2y Combine like terms: 2y + -2y = 0 -4x + 0 = 3 + -2y -4x = 3 + -2y Divide each side by '-4'. x = -0.75 + 0.5y Simplifying x = -0.75 + 0.5y
| 5.08cm=in | | -3x+8+4y-11-14x= | | x+(10(x/5))+(40(x/5))=165 | | 500ml=pt | | 5x^2-10x-y+9=0 | | 2500-x+x+22x=93500 | | 32=700w/5476 | | -3-10=8x+14-7x | | 18=700w/5476 | | h=-16t^2+70t+4 | | -11-25x=32x | | 1-2n=15 | | 2x^2-21x=-3x^2-5x-12 | | -7(3b+3)+22b-7=0 | | 4s-8=16 | | -5-25x-40-10=32x | | 12x-3+6x= | | 4(x+1)+2x=3x+1 | | 2.3q-1.1-4.5q=-3.2q-5.6 | | 3/t+7=5/-8 | | -5(1+5x)+5(-8x-2)=-4x-8x | | 17h-5h=36 | | 9/3x-1+5x/2x+3 | | -2uw+6u+uw-3u= | | -5/8*-6 | | 40-4b=-12-30b | | 4x^2-28x=-3x^2-5x-18 | | (3x+7)(x-2)=0 | | 7y-9=26 | | -26-4v=-3v-6+3v | | 10d+40=14d+56 | | 12+6x=-2x-4 |